Metode Mengajar dan Minat Siswa Dalam Meningkatkan Hasil Belajar Bahasa Arab - Muslim Iqbal Ramadhoni; Hari Setiadi (Sekolah Pascasarjana Universitas Muhammadiyah Prof. DR. Hamka bekerjasama dengan Himpunan Evaluasi Pendidikan Indonesia (HEPI)., 2016)
Penelitian bertujuan untuk mengungkap pengaruh metode mengajar dan minat belajar siswa terhadap hasil belajar bahasa Arab. Penelitian kuasi eksperimen ini menggunakan rancang dua faktor treatment by level design, dengan teknik analisis ANOVA dua jalan. Sampel 48 siswa. Hasil penelitian menunjukan adanya perbedaan hasil belajar bahasa Arab yang signifikan antara siswa yang diajar dengan metode Functional Notional dengan yang diajar dengan metode Audiolingual. Terdapat pengaruh interaksi metode mengajar dan minat siswa terhadap hasil belajar bahasa Arab. Berdasar hasil analisis, besar pengaruh variabel metode mengajar, minat siswa, interaksi metode mengajar dan minat siswa terhadap hasil belajar bahasa Arab sebesar 58.20%. Hasil Belajar bahasa Arab siswa yang diajar dengan metode Functional Notional lebih tinggi dari pada dengan metode Audiolingual untuk siswa yang minat belajarnya tinggi. Hasil belajar bahasa arab siswa yang diajar dengan metode Functional Notional lebih rendah dari pada dengan metode Audiolingual untuk siswa yang minat belajarnya rendah. Implikasi, keberhasilan pembelajaran bahasa Arab terkait kesesuaian metode mengajar dengan materi ajar, dan keadaan siswa. Dalam pembelajaran, guru bahasa Arab harus menyesuaiakn metode mengajar dengan minat siswa. Bagi siswa yang sangat berminat, lebih tepat jika diajar dengan metode Functional Notional, bagi siswa yang kurang berminat, dengan metode Audiolingual. The study aims to reveal the influence of teaching methods and students’ interests in learning Arabic language. The quasi-experimental study uses a two treatment designs by level design, with two-way ANOVA. Sample 48 students. The results show that there are differences in learning achievement of Arabic language significantly between students taught with Functional Notional method and students taught with audio-lingual method. Secondly, there is an interaction effect of teaching methods and students’ interests toward learning achievement of Arabic language. It appears from the results of the analysis on the major effect of methods of teaching, students’ interests, teaching methods interaction and students' interest towards learning achievement of Arabic language by 58.20%. Thirdly, the groups of students taught with Functional Notional method is higher than group of students taught with audio-lingual method for the students with a strong interest. Fourthly, Arabic language learning achievement of the students taught with Functional Notional method is lower than in the group of students taught with audio-lingual method for the students with lower interest. The findings in this study implies that the success of Arabic language learning in school is closely associated with the ability of teachers in selecting appropriate teaching methods as needed, teaching materials, student circumstances and conditions. Arabic language teacher in the language learning process should be encouraged to synchronize the interests of students and teaching methods used. For students who have a high interest, the Arabic teacher is suitable to use Notional Functional methods and for students with low interest is appropriate to use audio- lingual method.